2004
DOI: 10.1002/marc.200300162
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Catalytic System for the Synthesis of Ethylene–Hex‐1‐ene Copolymers from Ethylene Stock

Abstract: Summary: A tandem catalytic system, composed of (η5‐C5H4CMe2C6H5)TiCl3 (1)/MMAO (modified methyl aluminoxane) and [(η5‐C5Me4)SiMe2(tBuN)]TiCl2 (2)/MMAO, was applied for the synthesis of ethylene–hex‐1‐ene copolymers with ethylene as the only monomer stock. During the reaction, 1/MMAO trimerized ethylene to hex‐1‐ene, while 2/MMAO copolymerized ethylene with the in situ produced hex‐1‐ene to poly(ethylene–hex‐1‐ene). By changing the catalyst ratio and reaction conditions, a series of copolymer grades with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Recently, we used a tandem catalyst system comprising of an ethylene trimerization catalyst, (Z (2)/MMAO, for the successful synthesis of LLDPE of n-butyl branches with ethylene as the only monomer stock. [28,29] In this work, we carried out a further investigation on the melt rheological properties of LLDPE prepared with this tandem catalysis system and the results reported here show convincingly the presence of a sparse level of LCB in these polymers. This work hence demonstrates that LCB LLDPE can be obtained from ethylene as the sole monomer using this unique tandem catalysis system that comprises a CGC catalyst having high macromonomer generation and incorporation ability.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Recently, we used a tandem catalyst system comprising of an ethylene trimerization catalyst, (Z (2)/MMAO, for the successful synthesis of LLDPE of n-butyl branches with ethylene as the only monomer stock. [28,29] In this work, we carried out a further investigation on the melt rheological properties of LLDPE prepared with this tandem catalysis system and the results reported here show convincingly the presence of a sparse level of LCB in these polymers. This work hence demonstrates that LCB LLDPE can be obtained from ethylene as the sole monomer using this unique tandem catalysis system that comprises a CGC catalyst having high macromonomer generation and incorporation ability.…”
Section: Introductionsupporting
confidence: 75%
“…[28,29] The synthesis was carried out in a 500 mL glass reactor equipped with a magnetic stirrer under atmospheric pressure of ethylene. Typical synthesis procedure is as follows:…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…By adjusting the two catalyst ratio or varying reaction temperature from 25 to 70 8C, butyl branched PE samples having various melting temperatures (T m ) 48.6-128.7 8C and degrees of crystallinity (X c ) 7.6-56.9% were prepared. [3][4][5] Lu and coworkers [6,7] prepared polyethylene with branches mainly from ethyl to hexyl using ZieglerNatta catalyst and [(2-ArN C(CH 3 )) 2 C 5 H 3 N]FeCl 2 with MAO as co-catalyst at 30-70 8C. The products possessed T m 's from 115.5 to 124.0 8C and X c 's from 7.2 to 40%.…”
Section: Introductionmentioning
confidence: 98%
“…After that, a wide variety of promising tandem catalytic systems have been developed to prepare LLDPE in situ involving two different Ziegler-Natta catalysts, Ziegler-Natta catalyst/ homogeneous catalyst, two or three different homogeneous catalysts. [3][4][5][6][7][8][9][10] Surveying these works, [11][12][13][14][15][16] it is found that tandem catalysis is consisted of two kinds of catalysts and one activator, in which one catalyst oligomerizes the ethylene to a-olefins, and the other is responsible for polymerizing the ethylene and incorporating the a-olefins into the growing polymer chain under the same activator. In other words, the essential of tandem catalysis exists a dual functional catalyst active species: oligomerization/copolymerization active species in the same reaction system.…”
Section: Introductionmentioning
confidence: 99%